Crystallization Behavior of Rapid-Compression-Induced Mesomorphic Isotactic Polypropylene during Uniaxial Stretching at Different Temperatures. (26th May 2022) - Xu, Mingkun; Lin, Jiaxiang; Zhang, Xiaolin; Li, Zhenyin; Liu, Chuntai; Shen, Changyu; Shao, Chunguang
Abstract : The uniform bulk mesomorphic iPP is prepared by rapid compression, and its structural evolution under stretching at different temperatures is studied by combining wide-angle X-ray diffraction and small-angle X-ray scattering. Results show that stretching can induce mesophase to crystallize into α -phase or promote this phase transformation synergistically with temperature, which depends on the selection of stretching temperature. When the temperature is lower than the glass transition temperature of rigid amorphous fraction (RAF), stress could make RAF devitrify firstly and then induce meso- α phase transition during the strain-softening process. As the temperature increases, the high temperature could induce meso- α phase transition to occur before the strain softening, while stretching could promote this transition. When the temperature is higher than a critical value around 100°C, the mesophase can be transformed into α -phase completely during stretching. SAXS results show that all the transformed α -crystal exhibits nodular morphology, and they are ductile with greatly enhanced deformability. Based on the results, a reasonable mechanism of meso- α transformation in the stretching process is proposed, explaining the phase transition that goes through several different steps.